Micromechanics of granular materials : proceedings of the U.S./Japan Seminar on the Micromechanics of Granular Materials, Sendai-Zao, Japan, October 26-30, 1987 - Satake, Masao; Jenkins, James T., 1942- (Studies in applied mechanics, 1988)
This proceedings volume contains papers from researchers in Japan, the United States and England who have made fundamental contributions to the micromechanics of granular materials. The purpose of the seminar was to facilitate an exchange of ideas between scientists working with statistical and continuum theories, computer simulations and experiments on both static and dynamic behaviour. In describing the solid like behaviour of granular materials, many new ideas on the constitutive relations are introduced in this volume. As an application of the analysis, the mechanism of liquefaction is discussed. Computer simulations have become a vital tool in establishing the micromechanical approaches which otherwise would not be experimentally tested. In numerical simulations and theoretical analyses of rapid granular flow, various modifications on the nature of materials and boundaries are given. Possible applications of the techniques of the stereology and analysis based on geometrical statistics are also included. The papers collected in this volume signify that the promotion of a good understanding of the mechanics of granular materials has been and will continue to be valued in a variety of technical disciplines.